The Concepts of Population and Sampling in Quantitative Research and the Selection of Participants/Key Informants in Qualitative Research - Agung Aripandu Andaristo; Naf’an Tatihoran; Rizal Firdaus (Universitas Al-Hikmah Indonesia, 2025)
This research discusses the concepts of population and sampling in quantitative research, as well as the selection of participants/key informants in qualitative research. The aim of this study is to provide a clear understanding of these concepts and how they are applied in different research methods. The method used in this research is a literature review, analyzing relevant and reliable sources. The results show that in quantitative research, the population refers to the entire group being studied, while sampling is the technique used to select a representative sample from the population. In contrast, qualitative research emphasizes the selection of participants/key informants who are considered to have in-depth and relevant information related to the research topic. Further discussion reveals the importance of selecting the right sample or informant to ensure the validity and relevance of the data obtained. In conclusion, sampling in quantitative research should follow strict procedures to ensure the results are generalizable, while selecting informants in qualitative research prioritizes the depth and quality of the information gathered.